Spatial patterns of unburned refugia in Siberian larch forests during the exceptional 2020 fire season. Issue 10 (22nd May 2022) - Talucci, Anna C.; Loranty, Michael M.; Alexander, Heather D.
Abstract: Aim: Wildfire is an essential disturbance agent that creates burn mosaics, or a patchwork of burned and unburned areas across the landscape. Unburned patches, fire refugia, serve as carbon sinks and seed sources for forest regeneration in burned areas. In the Cajander larch ( Larix cajanderi Mayr.) forests of north‐eastern Siberia, an unprecedented wildfire season in 2020 and little documentation of landscape patch dynamics have resulted in research gaps about the characteristics of fire refugia in northern latitude forests, which are warming faster than other global forest ecosystems. We aim to characterize the 2010 distribution of fire refugia for these forest ecosystems and evaluate their topographic drivers. Location: North‐eastern Siberia across the North‐east Siberian Taiga and the Cherskii‐Kolyma Mountain Tundra ecozones. Time period: 2001–2020. Major taxa studied: Cajander larch. Methods: We used Landsat imagery to define burned and unburned patches, and the Arctic digital elevation model to calculate topographic variables. We characterized the size and density of fire refugia. We sampled individual pixels ( n = 80, 000) from an image stack that included a binary burned/unburned, elevation, slope, aspect, topographic position index, ruggedness, and tree cover from 2001 to 2020. We evaluated the topographic drivers of fire refugia with boosted regression trees. Results: We found no substantial difference in fire refugia size and density across the region. The fire refugia size averaged 7.2 ha (0.09–150, 439 ha). The majority of interior burned patches exceed the potential wind dispersal distance from fire refugia. Topographic position index and terrain steepness were important predictors of fire refugia. Main conclusions: Unprecedented wildfires in 2020 did not impact fire refugia formation. Fire refugia are strongly controlled by topographic positions such as uplands and lowlands that influence microsite hydrological conditions. Fire refugia contribute to postfire landscape heterogeneity that preserves ecosystem functions, seed sources, habitat, and carbon sinks.